Deformation and damage behavior of the deep concrete cut-off wall in core earth-rock dam foundation based on plastic damage model - A case study. (December 2022) - Guan, Zhixuan; Sun, Xinjian; Zhang, Guangli; Li, Guochao; Huang, Peijie; Zhang, Baoyun; Wang, Jiwei; Zhou, Xinjie
Abstract: Concrete cut-off walls are widely used as an effective anti-seepage technique in overburden dam foundations all over the world. The deep cut-off wall in a core earth-rock dam foundation is often subjected to complex force conditions, and may have to withstand large stresses and deformations. In certain circumstances, it can even face the risk of cracking damage. Thus, it is of a great importance to clarify the mechanical properties and cracking trend of the deep cut-off wall of core earth-rock dam on the overburden foundation. In this paper, a simple plastic damage model for the damage analysis of deep cut-off wall was proposed under the framework of Lee-Fenves Model. In this model, the tensile and compressive responses of the wall were characterized by employing the tensile and compressive constitutive relations based on fracture energy, and different tensile and compressive damage evolution processes were considered based on the damage factor introduced according to the Sidoroff energy equivalence principle. Further, by taking into account the plastic damage, the wall-soil contact effect and the rock mass plasticity, a numerical model was established to investigate the stress deformation and damage properties of a 92-m-deep cut-off wall of a core earth-rock dam, in order to validate the feasibility and rationality of the proposed model in describing the nonlinear mechanical behavior and failure trend of the cut-off wall. Moreover, the impact of hidden faults and constraints on the mechanical properties of cut-off wall was also discussed in detail.